2017
DOI: 10.4055/cios.2017.9.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Arthroplasty: Early Results and Functional Outcome of the Zimmer Gender Solutions Patello-Femoral Joint System

Abstract: BackgroundImproved knee prosthesis designs have led to an increase in the use of patellofemoral arthroplasty as a primary treatment option in recent times. We report the early results and outcomes of the Zimmer Gender Solutions Patello-Femoral Joint (PFJ) system used to treat isolated patellofemoral osteoarthritis (PFA).MethodsWe retrospectively reviewed and analysed data of patients who underwent PFJ replacement (PFJR) at our institution with a minimum follow-up of 2 years.ResultsMedian Oxford Knee score (OKS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…2016, Konan and Haddad 2016, Osarumwense et al. 2017, Odgaard et al. 2018), suggesting that PFA may be a good choice in suitably selected patients.…”
mentioning
confidence: 99%
“…2016, Konan and Haddad 2016, Osarumwense et al. 2017, Odgaard et al. 2018), suggesting that PFA may be a good choice in suitably selected patients.…”
mentioning
confidence: 99%
“…Although PFA has existed for 30 years, it is still controversial because of the high failure rate in the early design of trochlear prosthesis [22]. The improved second generation of PFA, such as Zimmer PFA [12], which achieved better clinical results and higher prosthesis survival. We found that the new implant jigs developed for this prosthesis was easy to use, accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of more and more anatomical PFA prosthesis designs, it can achieve better clinical results, higher patients satisfaction and prosthesis survival rate [11]. In the past four years, the second generation Zimmer gender PFA has been the most widely used patellofemoral prosthesis in Australia, with a 3-year cumulative revision rate of 5.3% [12]. As obesity and exercise-related injuries are expected to increase, more and more patients will need knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…The same surgical team performed all of the surgeries in accordance with standard surgical protocols. 25 An arthroscopic examination conducted before PFA to confirm that the presence of degenerative cartilage was limited to the patellofemoral joint. 16 PFA was performed through a standard medial parapatellar approach.…”
Section: Surgical Techniquesmentioning
confidence: 99%